2011
DOI: 10.1136/vr.d6412
|View full text |Cite
|
Sign up to set email alerts
|

Birnavirus‐associated proventriculitis in French broiler chickens

Abstract: detection of CPnv, smears of proventriculus from four birds were spotted onto FTa Cards (Whatman) and shipped to the Clinical virology Laboratory, north Carolina state University, Usa. The rT-PCr assays were positive for three of four samples, confirming the molecular detection of CPnv. The sequence of one PCr product showed 99 per cent nucleotide identity with the reference CPnv sequence (genBank accession number hM038436). as far as we are aware, this is the first documented case of CPnvassociated proventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Cases of chickens with lymphocytic and necrotizing proventriculitis, consistent with TVP, have been reported in the USA (Guy et al, 2011b), South Korea (Kim et al, 2015) and several countries in Europe (Kouwenhoven et al, 1978;Grau-Roma et al, 2010;Marguerie et al, 2011). However, as far as the authors are aware, this is the first peer-reviewed description of TVP as well as of CPNV in the UK.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Cases of chickens with lymphocytic and necrotizing proventriculitis, consistent with TVP, have been reported in the USA (Guy et al, 2011b), South Korea (Kim et al, 2015) and several countries in Europe (Kouwenhoven et al, 1978;Grau-Roma et al, 2010;Marguerie et al, 2011). However, as far as the authors are aware, this is the first peer-reviewed description of TVP as well as of CPNV in the UK.…”
Section: Discussionmentioning
confidence: 91%
“…TVP was first described in the Netherlands almost 40 years ago (Kouwenhoven et al, 1978). Since then, it has been reported in several countries in North America (Guy et al, 2011b;Noiva et al, 2015), Europe (Grau-Roma et al, 2010;Marguerie et al, 2011), and Asia (Kim et al, 2015). Since the emergence of the disease, there has been considerable discussion as to the aetiological agent responsible.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rst reports on TVP date back to 1978 and come from the Netherlands [2], when Kouwenhoven et al reported a case of proventriculitis in commercial chicken broilers and proved that TVP was induced by an infectious factor. Since then, TVP cases have been identi ed and reported in the USA, Australia, China, South Korea, Spain, France, the UK, and Poland among other countries [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%